PENGARUH KOMUNIKASI PEMASARAN TERPADU DAN EKUITAS MEREK TERHADAP LOYALITAS KONSUMEN - Darmawangsa, Anak Agung Bagus; Sri Ardani, I Gusti Agung Ketut (E-Jurnal Manajemen, 2015)
800x600 Loyalty is the priceless asset for the company. Nowadays, especially in the hard battle of communication business, the company used many strategic ways to keep the existence of their customers for using their products. Doing of this research is to test the cause of integrated marketing communication and brand equity to customer loyalty in Denpasar. The location of this research, placed in many provider agent that spreaded around Denpasar, with cluster sampling technique and used 115 respondent. With double regression analysis, shows the coefficient regression of integrated marketing communication (X 1 ) is 0,442 and the coefficient regression of brand equity (X 2 ) is 0,314. The conclusion for the company is to build and protect the massive strategy of integrated marketing communication and brand equity, to get the maximum costumer loyalty. Keyword : Customer loyalty, integrated marketing communication, brand equity. Normal 0 false false false EN-US X-NONE X-NONE
Keywords: customer loyalty; integrated marketing communication; brand equity